If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2a + 2b + b = 0 Combine like terms: 2b + b = 3b -2a + 3b = 0 Solving -2a + 3b = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3b' to each side of the equation. -2a + 3b + -3b = 0 + -3b Combine like terms: 3b + -3b = 0 -2a + 0 = 0 + -3b -2a = 0 + -3b Remove the zero: -2a = -3b Divide each side by '-2'. a = 1.5b Simplifying a = 1.5b
| 8z-24=0 | | 2(18+w)=56 | | -4.4s-2=-5-4.2 | | 82-29=18 | | 180=x+50+(180-4x-40) | | 81=a^2 | | r-33-2=11 | | 144=-2-6(6)6(10) | | 8t-2=33+t | | 2k+2=-1313k | | 4K=-9k | | 144=-2-6(6+10) | | 130=3x+2y | | 5x+1+4=11+9x | | 3m+2m+4n+3n= | | 9/4x=1/16 | | 2/3x=140 | | 1=12x-8 | | 5x+8=6x-18 | | 10/9c=-81 | | P-3.2=7.6 | | 7.3y-5.8=51.9 | | 53-2x=5x-17 | | 15+9n=9-n | | 2(7x+2)=-12 | | 2/3z=1/21 | | 50=5ln(3x+7) | | 84=2*35+2*w | | X(8-1)=18 | | -1=2x-8 | | -x/4-5=-8 | | -15+t=20 |